Incidence of kidney stones in pregnancy and associations with adverse obstetrical outcomes: a systematic review and meta-analysis of 4.7 million pregnancies. (12th December 2022) - Kirubarajan, Abirami; Taheri, Cameron; Yau, Matthew; Aggarwal, Reenika; Lam, Andrew C. L.; Golda, Nicole; Buckley, Roger
Abstract: Background: Renal stones are a common cause of non-obstetrical abdominal pain in pregnant women. Though the management of renal stones in pregnancy is challenging, it remains unclear how the incidence of kidney stones may affect the course of pregnancy and delivery. Objective: To determine the incidence of renal stones in pregnancy and its impact on adverse obstetrical outcomes. Data sources: We conducted a systematic literature search of three databases: Ovid MEDLINE, Ovid EMBASE, and EBSCO CINAHL Plus. After the selection of articles, an additional hand-search of their citations was completed to maximize sensitivity. Databases were examined from the last four decades (19 March 1970) up to the search date (19 March 2020). Study eligibility criteria: Articles were excluded if they were not relevant to kidney stones or did not report outcomes related to pregnancy. Case reports, animal studies, and cadaveric studies were excluded. Conference abstracts, gray literature, and unpublished data were not eligible. Study appraisal and synthesis methods: All screening, extraction, and synthesis were completed in duplicate with two independent reviewers. All outcomes reported in the included studies were systematically evaluated to determine suitability for meta-analysis. Random-effects models and sensitivity analyses were used to account for interstudy variation. Renal stone incidence rates were pooled to generate summary proportions. Risk of bias assessment was completed using the Risk of Bias Assessment tool for Non-randomized Studies. Results: Twenty-one studies were included through systematic review and approximately 4.7 million pregnancies across nine studies were included for meta-analysis. There are three major findings of this review regarding renal stone incidence in pregnancy and maternal, child, and birth-related outcomes associated with renal stones. First, we found pooled incidence of renal stones was 0.49%, or one case for every 204 pregnancies. Second, renal stones during pregnancy were significantly associated with the development of preeclampsia and urinary tract infection, as well as increased likelihood of low birth weight, preterm labor, and C-section deliveries. However, renal stones were not significantly associated with premature rupture of membranes or infant mortality. Third, there were limited obstetrical complications reported with either medical or surgical therapies although comparative outcomes were not provided in the majority of studies, precluding formal meta-analysis. Conclusions: Although renal stones in pregnancy are relatively rare, there may be an associated risk of serious adverse obstetrical outcomes. However, further research is required to understand whether these obstetrical outcomes are causal or due to other confounders. Interdisciplinary care and pregnancy-specific counseling should be advised for pregnant women with kidney stones.